Radiolabeled curcumin as β amyloid imaging and tumor targeting imaging agents - Nurmaya Effendi (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
Curcumin, a polyphenolic compound, derived from the rhizomes of Curcuma longa L. Curcumin shows potential pharmacological action against numerous disorders, including cancer, neurodegenerative, and infection diseases. Curcumin-based molecular imaging agents could be useful for early detection of Alzheimer Disease and tumor and monitor the progress of therapy. Radiolabeled curcumin and its derivatives become promising compounds as imaging agents. In this review, radiolabeled curcumin bearing radionuclides including fluorine-18, Technetium-99m, Iodine-125, and Gallium-68 are reviewed as an effort to develop curcumin-based probes not only for β amyloid imaging but also for tumor imaging.